Sodium acrylate modified hard carbon negative electrode material, preparation method thereof and sodium ion battery

CN122889719APending Publication Date: 2026-10-09XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611045189.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种丙烯酸钠修饰硬碳负极材料及其制备方法、钠离子电池,以解决现有硬碳负极首次放电过程中电解液无序分解、界面膜厚且不均匀、不可逆钠损失严重以及长期循环稳定性不足的问题

Benefits of technology

(1)本发明采用水溶液法对硬碳进行丙烯酸钠修饰,无需高温烧结、气相沉积或活泼金属预钠化,制备工艺简单、条件温和。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889719A_ABST
    Figure CN122889719A_ABST
Patent Text Reader

Abstract

The application relates to the field of sodium ion battery negative electrode materials, and discloses a sodium acrylate modified hard carbon negative electrode material, a preparation method thereof and a sodium ion battery. The sodium acrylate is dissolved in a solvent, hard carbon is added and fully mixed, evaporation and vacuum drying are carried out, the sodium acrylate is distributed in the defects, edges and open hole areas on the surface of the hard carbon, and the sodium acrylate modified hard carbon negative electrode material is obtained. In the first discharge process, the C=C double bond of the sodium acrylate is subjected to interface electrochemical conversion, a polymer derivative interface skeleton is formed, a thin and uniform stable solid electrolyte interface film is induced to be formed, the continuous decomposition of electrolyte is inhibited, and the irreversible sodium consumption is reduced. The preparation method is simple, the conditions are mild, the obtained material has high initial coulomb efficiency, excellent rate performance and long cycle stability, and can be used for sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery anode materials and electrode / electrolyte interface control technology, specifically relating to a sodium acrylate modified hard carbon anode material and its preparation method, and sodium-ion batteries. Background Technology

[0002] Sodium-ion batteries have advantages such as abundant sodium resources, low cost, and suitability for large-scale energy storage. Hard carbon has suitable sodium storage potential, high reversible capacity, and a good foundation for large-scale preparation, making it a promising anode material for sodium-ion batteries.

[0003] However, hard carbon surfaces typically contain defects, edge sites, oxygen-containing functional groups, and open pores. During the initial discharge, these highly active regions easily induce non-uniform decomposition of the electrolyte, forming a thick, unevenly distributed solid electrolyte interfacial film and consuming a large amount of active sodium, resulting in a low initial coulombic efficiency. During cycling, the unstable interfacial film may also crack, detach, and regenerate, causing continuous electrolyte and sodium consumption, increased interfacial impedance, and capacity decay.

[0004] Existing surface coating, artificial interface films, and pre-sodiumization technologies can improve the above problems to some extent, but rigid inorganic coating layers may have interfacial mismatch, some pre-sodiumization materials are sensitive to water and air and have complex processes, and ordinary organic modification layers are difficult to simultaneously achieve interfacial chemical regulation, mechanical stability, and mitigation of irreversible sodium loss.

[0005] Therefore, there is a need for a hard carbon anode material that is simple to prepare, has mild conditions, and can control the formation of the interface film in situ during the first discharge. Summary of the Invention

[0006] The purpose of this invention is to provide a sodium acrylate-modified hard carbon anode material and its preparation method, as well as a sodium-ion battery, to solve the problems of disordered electrolyte decomposition, thick and uneven interfacial film, severe irreversible sodium loss, and insufficient long-term cycle stability during the first discharge of existing hard carbon anodes.

[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a sodium acrylate-modified hard carbon anode material, comprising the following steps: (1) Dissolve sodium acrylate in a solvent to obtain a sodium acrylate solution; (2) Add hard carbon to the sodium acrylate solution and mix, so that sodium acrylate is adsorbed and / or enriched on the defect sites, edge sites and open pore areas of the hard carbon surface; (3) Remove the solvent and dry to obtain sodium acrylate modified hard carbon anode material with a sodium acrylate content of 3 to 10 wt%.

[0008] As a further preferred technical solution of the present invention, the solvent in step (1) is water or an aqueous polar solvent; the aqueous polar solvent includes a mixed solvent formed by at least one of water and methanol, or water and ethanol, wherein the volume fraction of water is preferably not less than 50%.

[0009] As a further preferred technical solution of the present invention, in step (1), 0.03-0.1g of sodium acrylate is added for every 20mL of solvent.

[0010] As a further preferred technical solution of the present invention, in step (1), sodium acrylate is dissolved in a solvent and stirred at 15-35°C for 0.5-3 hours to form a sodium acrylate solution.

[0011] As a further preferred technical solution of the present invention, in step (3), the solvent is removed by evaporation at 50-80°C under continuous stirring.

[0012] As a further preferred technical solution of the present invention, vacuum drying is carried out in step (3) at 80-130°C for 6-24 hours.

[0013] According to a second aspect of the present invention, the present invention also provides a sodium acrylate modified hard carbon anode material, which is prepared by the preparation method described in the first aspect.

[0014] According to a third aspect of the present invention, the present invention also provides a sodium-ion battery, comprising a negative electrode sheet comprising a sodium acrylate modified hard carbon negative electrode material according to the second aspect.

[0015] As a further preferred embodiment of the present invention, the sodium acrylate is adsorbed and / or enriched in the defects, edges, and open pore regions of the hard carbon surface in monomer form, and undergoes interfacial confined in-situ electropolymerization and / or crosslinking through carbon-carbon double bonds during the first discharge of the battery to form a polymer-derived interfacial framework. This interfacial framework participates in and regulates the nucleation and growth of the solid electrolyte interfacial film, thereby inducing the formation of a thin, uniform, and continuous solid electrolyte interfacial film. This process differs from directly coating hard carbon with pre-prepared sodium polyacrylate.

[0016] In the sodium acrylate-modified hard carbon anode material prepared by the method of this invention, sodium acrylate undergoes adsorption and local interaction with defect sites, oxygen-containing functional groups and open pore regions on the surface of hard carbon through sodium carboxylate groups, thereby preferentially distributing in the highly active regions of the hard carbon surface. This enables the carbon-carbon double bonds in sodium acrylate to undergo interfacial electrochemical transformation during the first discharge of the sodium-ion battery, forming a polymer-derived interfacial framework to regulate the nucleation and growth of the solid electrolyte interfacial film.

[0017] When the sodium acrylate-modified hard carbon anode material of this invention is applied to sodium-ion batteries, it can induce the formation of a thin, uniform, continuous, and NaF-enriched solid electrolyte interfacial film, improve the mechanical integrity and stability of the interfacial film, inhibit the continuous decomposition of the electrolyte and the repeated rupture and reconstruction of the interfacial film, and reduce the irreversible sodium consumption during the first charge and discharge process, thereby improving the first coulombic efficiency, reversible capacity, rate performance and cycle stability of sodium-ion batteries.

[0018] Compared with the prior art, the present invention can achieve the following beneficial effects: (1) The present invention uses an aqueous solution method to modify hard carbon with sodium acrylate, which does not require high-temperature sintering, vapor deposition or pre-sodiumization of active metals. The preparation process is simple and the conditions are mild.

[0019] (2) In the preparation method of the present invention, sodium acrylate can be preferentially distributed in the defects, edges and open pore areas of the hard carbon surface, and can regulate the highly active interface area without significantly changing the microcrystalline structure of the hard carbon body.

[0020] (3) The negative electrode material of the present invention undergoes interfacial electrochemical transformation of sodium acrylate and forms a polymer-derived interfacial skeleton during the first discharge, which can guide the uniform nucleation and growth of the solid electrolyte interfacial film.

[0021] (4) The interfacial film obtained by the present invention is thin, continuous and uniform, which can inhibit the continuous decomposition of electrolyte and the cracking and repeated generation of interfacial film.

[0022] (5) In this invention, the side reaction suppression and the participation of sodium-containing groups of sodium acrylate in the initial interface reaction produce a synergistic effect, which can improve the first coulombic efficiency, rate performance and cycle stability. Attached Figure Description

[0023] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0024] Figure 1 The images show the XRD patterns of the sodium acrylate-modified hard carbon materials prepared in Examples 1-4 and the hard carbon material in Comparative Example 1.

[0025] Figure 2 The images show the FTIR spectra of the sodium acrylate-modified hard carbon material prepared in Example 2 before and after cycling.

[0026] Figure 3 HRTEM images of (a) the sodium acrylate-modified hard carbon material prepared in Example 2 and (b) the hard carbon material of Comparative Example 1 after cycling.

[0027] Figure 4 The first CV curves are for the sodium acrylate-modified hard carbon material prepared in Example 2 and the hard carbon material in Comparative Example 1.

[0028] Figure 5 The first charge-discharge curves are shown for the sodium acrylate-modified hard carbon material prepared in Example 2 and the hard carbon material in Comparative Example 1.

[0029] Figure 6 Cyclic performance graphs of sodium acrylate modified hard carbon materials prepared in Examples 1-4 and hard carbon materials in Comparative Examples 1-3 are shown.

[0030] Figure 7 The rate performance graphs show the sodium acrylate modified hard carbon materials prepared in Examples 1-4 and the hard carbon material in Comparative Example 1.

[0031] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0032] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0033] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the reagents and materials used in the following embodiments are conventional commercially available reagents and materials; and the experimental methods described are conventional methods unless otherwise specified.

[0034] Example 1 This embodiment provides a method for preparing a sodium acrylate-modified hard carbon anode material, comprising the following steps: Weigh 0.97 g of commercial hard carbon. Add 0.03 g of sodium acrylate to 20 mL of deionized water and stir at 25 °C for 1 h to form a homogeneous solution. Add the hard carbon to the solution and continue stirring to ensure thorough dispersion. Then raise the temperature to 60 °C and gradually evaporate the water while stirring. Collect the resulting solid and vacuum dry at 110 °C for 12 h to obtain a negative electrode material with a sodium acrylate content of 3 wt%.

[0035] Example 2 Except for the amount of sodium acrylate (0.05g) and hard carbon (0.95g), the remaining steps are the same as in Example 1, and a negative electrode material with a sodium acrylate content of 5wt% is obtained.

[0036] Example 3 Except for the amount of sodium acrylate (0.07g) and hard carbon (0.93g), the remaining steps are the same as in Example 1, and a negative electrode material with a sodium acrylate content of 7wt% is obtained.

[0037] Example 4 Except for the amount of sodium acrylate (0.10g) and hard carbon (0.90g), the remaining steps are the same as in Example 1, and a negative electrode material with a sodium acrylate content of 10wt% is obtained.

[0038] Comparative Example 1 Commercial hard carbon from the same source as in Examples 1-4 was used directly, but without sodium acrylate treatment, as an unmodified blank control.

[0039] Comparative Example 2 Except for replacing sodium acrylate with sodium itacate in equal molar amounts, the remaining steps are the same as in Example 2, and a sodium itacate-modified anode material is obtained.

[0040] Comparative Example 3 Except for replacing sodium acrylate with sodium cinnamate in equal molar amounts, the remaining steps are the same as in Example 2, resulting in a negative electrode material modified with sodium cinnamate.

[0041] The physical properties of the sodium acrylate-modified hard carbon anode materials prepared in Examples 1-4 were characterized. Figure 1 The XRD patterns of the sodium acrylate-modified hard carbon materials prepared in Examples 1-4 and the hard carbon material of Comparative Example 1 are shown. It was observed that sodium acrylate-related diffraction peaks appeared at about 30° in Examples 1-4, and the diffraction peaks increased with the increase of sodium acrylate content.

[0042] Battery Assembly and Testing: The sodium acrylate-modified hard carbon anode material prepared in Examples 1-4 was mixed with conductive carbon black and binder polyvinylidene fluoride at a mass ratio of 8:1:1 and dispersed in N-methylpyrrolidone. The mixture was then uniformly coated onto a copper foil surface, and solvent evaporation was performed to prepare the anode sheet. A sodium metal sheet was used as the counter electrode, a glass fiber membrane as the separator, and a 1 mol / L electrolyte was used. -1 A coin cell sodium-ion battery was assembled using a 1,2-ethylene glycol dimethyl ether (DME) solution of NaPF6 for testing. Meanwhile, an electrode was prepared and a battery was assembled using the same method with the unmodified hard carbon anode material of Comparative Example 1 as a control.

[0043] Figure 2 These are the FTIR spectra of the sodium acrylate-modified hard carbon material prepared in Example 2 before and after cycling. After cycling, the value is located at 1561.7 cm⁻¹. -1 The disappearance of the C=C related vibration peak indicates that the vinyl group of sodium acrylate was consumed and underwent interfacial electrochemical transformation during the first discharge.

[0044] Figure 3 These are HRTEM images of the sodium acrylate-modified hard carbon material prepared in Example 2 and the hard carbon material in Comparative Example 1 after cycling. It can be seen that the interface film in Example 2 is continuous and uniform with a thickness of about 15.5 nm, while the interface film in Comparative Example 1 has an uneven thickness distribution and obvious thickening in local areas.

[0045] Figure 4 The first-cycle CV curves of the sodium acrylate-modified hard carbon material prepared in Example 2 and the hard carbon material in Comparative Example 1 show that the peaks of the side reactions in Example 2 are weakened during the first discharge.

[0046] Figure 5 The figures show the first-cycle charge-discharge curves of the sodium acrylate-modified hard carbon material prepared in Example 2 and the hard carbon material in Comparative Example 1. It can be observed that the first-cycle coulombic efficiency of Example 2 is increased to 82.5%, and the initial discharge voltage plateau decreases. This indicates that sodium acrylate modification can suppress irreversible side reactions during the first discharge process, reduce active sodium consumption, and thus improve the first-cycle coulombic efficiency.

[0047] Figure 6 The graphs show the cycling performance of the sodium acrylate-modified hard carbon materials prepared in Examples 1-4 and the hard carbon materials in Comparative Examples 1-3. After 135 charge-discharge cycles, the capacities of Examples 1-4 were 251.5, 266.3, 248.7, and 239.8 mAh g, respectively. -1 Both are higher than the 206.8 mAh g of the unmodified hard carbon comparative example 1. -1 This indicates that sodium acrylate modification can effectively improve the cycling capacity and interfacial stability of hard carbon anodes. Example 2 showed the highest capacity, indicating that a 5 wt% sodium acrylate content can effectively balance the interfacial regulation effect and pore structure. Further increasing the sodium acrylate content resulted in a decrease in capacity, possibly related to excessive modification agent covering the pore openings and increasing ion transport resistance. The cycling capacities of Comparative Examples 2 and 3 were only 188.7 and 186.4 mAh g, respectively. -1 The results, compared to the embodiments, demonstrate that not all sodium-containing organic salts or sodium salts containing double bonds can achieve the technical effects of the present invention, further proving that the sodium acrylate monomer structure and its interfacial electrochemical transformation play a key role in improving the performance of cyclic sodium storage.

[0048] Figure 7 The figures show the rate performance of the sodium acrylate-modified hard carbon materials prepared in Examples 1-4 and the hard carbon material in Comparative Example 1. The reversible capacities of Example 2 at 0.1, 0.2, 0.5, 1, 2, and 4 C are 296.0, 280.0, 269.1, 261.1, 252.6, and 243.1 mAh g, respectively. -1 This is superior to Examples 1, 3, 4 and Comparative Example 1. The corresponding data are summarized in Table 1.

[0049] Table 1. Rate performance of hard carbon anode materials obtained in Examples 1-4 and Comparative Example 1 The data in the table show that in Example 1, with a low sodium acrylate content, the sodium acrylate was insufficient to fully cover the highly active areas such as defects, edges, and open pores on the hard carbon surface, resulting in limited control over side reactions and SEI formation. In Example 2, when the sodium acrylate content was increased to 5%, the active sites were more effectively passivated, and a uniform and stable interfacial film was induced, thus achieving the highest capacity. Further increases in sodium acrylate to 7% and 10% as in Examples 3 and 4 resulted in excessive sodium acrylate forming a thicker coating on the hard carbon surface, blocking some pores, or prolonging the formation of Na+. + The transport path increases ineffective mass and interfacial impedance, thereby reducing the available sodium storage sites and consequently decreasing capacity.

[0050] This invention addresses the problems of low initial coulombic efficiency, unstable interfacial film, and cycle degradation in hard carbon anodes. It employs sodium acrylate to modify the surface of hard carbon, causing the sodium acrylate to undergo interfacial electrochemical transformation during the first discharge, forming a sodium-containing polymer-derived framework. This promotes the formation of a thin, continuous, and stable solid electrolyte interfacial film. This effectively inhibits continuous electrolyte decomposition, reduces irreversible sodium consumption, and improves the initial coulombic efficiency, rate performance, and cycle stability of the hard carbon anode, demonstrating promising application prospects in sodium-ion batteries.

[0051] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.

Claims

1. A method for preparing a sodium acrylate-modified hard carbon anode material, characterized in that, Includes the following steps: (1) Dissolve sodium acrylate in a solvent to obtain a sodium acrylate solution; (2) Add hard carbon to the sodium acrylate solution and mix, so that sodium acrylate is adsorbed and / or enriched on the defect sites, edge sites and open pore areas of the hard carbon surface; (3) Remove the solvent and dry to obtain sodium acrylate modified hard carbon anode material with a sodium acrylate content of 3 to 10 wt%.

2. The method for preparing sodium acrylate-modified hard carbon anode material according to claim 1, characterized in that, The solvent in step (1) is water or an aqueous polar solvent; the aqueous polar solvent includes a mixed solvent formed by at least one of water and methanol or water and ethanol.

3. The method for preparing sodium acrylate-modified hard carbon anode material according to claim 1, characterized in that, In step (1), 0.03-0.1g of sodium acrylate is added for every 20mL of solvent.

4. The method for preparing sodium acrylate-modified hard carbon anode material according to claim 1, characterized in that, In step (1), sodium acrylate is dissolved in a solvent and stirred at 15–35°C for 0.5–3 h to form a sodium acrylate solution.

5. The method for preparing sodium acrylate-modified hard carbon anode material according to claim 1, characterized in that, In step (3), the solvent is removed by evaporation at 50–80°C under continuous stirring.

6. The method for preparing sodium acrylate-modified hard carbon anode material according to claim 1, characterized in that, In step (3), vacuum drying is carried out at 80-130℃ for 6-24 hours.

7. A sodium acrylate-modified hard carbon anode material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 6.

8. A sodium-ion battery, comprising a negative electrode, characterized in that, The negative electrode sheet comprises the sodium acrylate modified hard carbon negative electrode material as described in claim 7.

9. The sodium-ion battery according to claim 8, characterized in that, After the first discharge of the battery, the carbon-carbon double bonds in the sodium acrylate-modified hard carbon anode material undergo interfacial electrochemical transformation, forming a polymer-derived interfacial framework and inducing the formation of a thin and uniform solid electrolyte interfacial film.